Shotgun proteomic analysis of tiger milk mushroom (Lignosus rhinocerotis) and the isolation of a cytotoxic fungal serine protease from its sclerotium - Yap, H.Y.Y.; Fung, S.Y.; Ng, S.T.; Tan, C.S.; Tan, N.H. (Elsevier, 2015)
Ethnopharmacological relevance The sclerotium of Lignosus rhinocerotis (Cooke) Ryvarden (tiger milk mushroom) has been traditionally used as a complementary and alternative medicine for cancer treatment by the local communities of Southeast Asia. Despite the continuous research interest in its antiproliferative activity, the identity of the bioactive compound(s) responsible has yet to be determined. This study aims to bridge the gap in existing research literature by using proteomics approach for investigation of the nature of the anticancer substance of L. rhinocerotis. Aim of the study To elucidate the proteome of L. rhinocerotis TM02 sclerotium by protein mass spectrometry and to further isolate and identify the cytotoxic component(s) bearing anticancer potential. Materials and methods The proteome of L. rhinocerotis sclerotium was analyzed by label-free quantitative shotgun proteomics, using 1D-SDS-PAGE coupled with nano-ESI-LC-MS/MS based on the availability of its genome-sequence database. The cytotoxicity of L. rhinocerotis sclerotial extracts against human breast adenocarcinoma cells (MCF7) were assessed by MTT cytotoxicity assay prior to successive purification steps by a combination of gel filtration chromatography, ammonium sulfate precipitation, and anion exchange chromatography. Bioactive compound(s) in the extracts was identified by shotgun proteomics and N-terminal protein sequencing. Results Several proteins with interesting biological activities including lectins, fungal immunomodulatory proteins, and several antioxidant proteins were identified from the proteome of L. rhinocerotis. A cytotoxic protein fraction (termed F5) which was partially purified from its sclerotial cold water extract F5 shows two distinct bands of 31 and 36 kDa in reducing SDS-PAGE and exhibited potent selective cytotoxicity against MCF7 cells with IC50 value of 3.00±1.01 μg/ml. Both bands were identified to be serine protease by LC-MS/MS analysis. Phenylmethylsulfonyl fluoride, a specific serine protease inhibitor, inhibited both the proteolytic activity and cytotoxicity of F5, suggesting that the cytotoxicity of F5 is related to its protease activity. Conclusions This study provides the first comprehensive and semi-quantitative profiling of the proteome of L. rhinocerotis sclerotium. Further investigation into its selective cytotoxicity shows that a serine protease-like protein, termed F5, may be targeted for new anticancer agent development.